Intractable hypoglycemia in pregnancy - Gonsalves, Kavita Peter; J., Mallikarjun V.; Thomas, Annamma; Bantwal, Ganapathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Insulinomas are rare tumours developed from pancreatic beta cells; 27 cases of insulinoma associated with pregnancy have been reported till date, mostly diagnosed before the 16th week. Triad of insulinoma; hypoglycemic symptoms, plasma glucose < 3.0 mmol/L, symptomatic relief with glucose administration. 28-year-old primi presented to us at 29 weeks with high BP and neuroglycopenic symptoms. Repeated episodes of loss of consciousness with hypoglycemia since 14 weeks. On evaluation diagnosed to have insulinoma and managed conservatively with dietary modifications, and medical treatment. She failed to respond and pregnancy was terminated due to high BP, hypoglycemia and Doppler changes. Delivered a stillborn girl at 31 weeks. Underwent laparotomy post-delivery for enucleation of the lesion. Quick normalization of sugar levels and overall recovery remarkable. Patient is on regular follow up. Insulinoma is a rare cause of severe repeated episodes of hypoglycemia early in pregnancy.